Analyzing the Influence of Sustainability Benefits on Chilean Consumers’ Intentions to Purchase Refurbished Smartphones - Kara, Ali; Spillan, John E.; Grunwald, Guido; Rojas Cabezas, German; Marquez Alvarez, Nicholas; Nocetti Nuñez, Victor Raul (Organizations and Markets in Emerging Economies, 2025)
This study examines the willingness of Chilean consumers to buy refurbished smartphones and how various benefits associated with these products, including sustainability advantages, influence their decision-making processes. Utilizing the consumer acceptance model for refurbished smartphones, data was collected through personal interviews with 190 consumers in a shopping mall setting. The findings indicate that the intention of Chilean consumers to purchase refurbished products is primarily driven by their subjective evaluations of perceived product value and risk as well as their positive brand evaluations. However, environmental concerns did not significantly impact purchase intentions. The study discusses both the theoretical and practical implications of these findings. By identifying enablers and barriers to sustainable consumption among Chilean consumers, our study complements research on the sustainability marketing of refurbished products in emerging markets. Furthermore, it adds to the literature on the evolution of circular economy approaches in emerging markets such as Chile, which differ in both socio-economic and cultural terms from more developed markets.